An application to Kato's square root problem - Toka Diagana (International Journal of Mathematics and Mathematical Sciences)
We find all complex potentials Q such that the general Schrödinger operator on ℝn, given by L=−Δ+Q, where Δ is the Laplace differential operator, verifies the well-known Kato's square problem. As an application, we will consider the case where Q∈Lloc1(Ω).